Ratios of effector to central memory antigen‐specific CD4+ T cells vary with antigen exposure in HIV+ patients. Issue 4 (4th February 2014) - Phetsouphanh, Chansavath; Xu, Yin; Bailey, Michelle; Pett, Sarah; Zaunders, John; Seddiki, Nabila; Kelleher, Anthony D
Abstract : The OX40/CD25 assay is a novel technique that assesses antigen‐specific CD4 + T‐cell responses. To unequivocally demonstrate that responding cells are memory cells that become activated after secondary stimulation, naïve CD45RA + and memory CD45RO + populations were stimulated with cytomegalovirus (CMV) lysate and the combined expression of CD25 and OX40 measured. As expected, the naïve population showed very little response, whereas there was a higher response from the memory counterpart. To further elucidate CD4 + memory T‐cell subsets involved in recall responses, CD4 + T cells were separated into central memory (Tcm) and effector memory (Tem) subsets and stimulated with antigen‐pulsed antigen‐presenting cells (APCs). CMV responses in healthy donors showed a Tem‐dominant response with a Tem/Tcm ratio of 1.2, whereas the tetanus toxoid responses were dominated by a Tcm response with a Tem/Tcm ratio of 0.35. To determine memory response in the chronic of HIV infection, patient samples were used. A similar pattern to healthy donors was observed in seven chronic HIV+ patients at week 4 after anti‐retroviral therapy who responded to CMV with a larger response coming from Tem. The pattern was similar after 48 weeks of therapy but the responses were lower in magnitude. In chronic HIV+ patients who respond to Gag peptides, following institution of therapy there was an inversion of the ratio of the responding memory subsets compared with week 4, with a greater response from Tcm at week 48. This result was concordant with reduction in antigen load. As immune activation decreased there was also a decrease in the percentage of responding effector memory cells and maintenance of long‐term central memory.